2018
DOI: 10.1159/000486672
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial, Cognitive, and Physical Impact of Elaborate Consultations and Life Review in Female Patients with Non-Metastasized Breast Cancer

Abstract: Background: Elaborate consultations and life review (ECLR) has been regularly applied in patients of various cancer entities and stages within Anthroposophic-integrative oncology concepts. However, a lack of systematic research in this field has been detected. To close this gap of knowledge, we evaluated the impact of ECLR in patients with non-metastasized breast cancer before, during, and after primary oncological treatment. Methods: Patient-reported outcome measures were evaluated by analyzing European Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
(47 reference statements)
3
15
0
Order By: Relevance
“…Components of the integrative medicine program at the GKH seem to have a favorable outcome on self-reported fatigue of breast cancer patients ( Table 5 ). In line with our previous analyses that ECLR was associated with relevant improvements of HRQL, 23 here we observed that receiving ECLR was also associated with significant improvements of physical and affective fatigue symptoms. In our approach demographic variables were considered and we monitored that the body mass index has a significant influence on the CFS-D scales.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Components of the integrative medicine program at the GKH seem to have a favorable outcome on self-reported fatigue of breast cancer patients ( Table 5 ). In line with our previous analyses that ECLR was associated with relevant improvements of HRQL, 23 here we observed that receiving ECLR was also associated with significant improvements of physical and affective fatigue symptoms. In our approach demographic variables were considered and we monitored that the body mass index has a significant influence on the CFS-D scales.…”
Section: Discussionsupporting
confidence: 93%
“…Primary NO breast cancer patients who were seen at the certified Breast Cancer Centre GKH, Berlin, Germany between June 2012 and April 2019, were screened as previously reported. 23 , 28 , 29 According to the German National Cancer Plan social services and psycho-oncological support were offered to all patients. At first diagnosis during the hospital stay, the patient received standard therapies in conjunction with integrative ones and appointments with NPI therapists were arranged in a personalized manner as described in detail previously.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a prospective observational study for primary stage I-III breast cancer patients as reported previously [ 30 , 31 ]. Patients who gave written consent to be registered in the Network Oncology (NO) registry [ 32 ], who were diagnosed between June 2012 and April 2017 at the certified Breast Cancer Centre (Gemeinschaftskrankenhaus Havelhöhe, Berlin, Germany), and who received a tumor board advice for CTX were included.…”
Section: Methodsmentioning
confidence: 99%
“…For the present evaluation, as similarly reported previously, 27,28,30 primary nonmetastasized breast cancer patients of the clinical database NO, who were seen at the certified Breast Cancer Center Gemeinschaftskrankenhaus Havelhöhe (GKH), Berlin, Germany, between June 2012 and October 2018, were screened. As the GKH actively supports shared decision-making, the patients have the chance to participate in the tumor board, and a joint recommendation for the therapy of the patient is given.…”
Section: Data Collectionmentioning
confidence: 99%